Kinematic contact-impact algorithm with friction - Wong, S.V.; Hamouda, A.M.S.; Hashmi, M.S.J. (Taylor and Francis Group, 2001)
This paper is devoted to the development of kinematic contact-impact algorithm for impact problems. The developed algorithm is based on conservation of momentum and coefficient of restitution. Node-node and node-element contacts are formulated. The algorithm includes a novel method forhandling potential voids and overlaps at contact intersection. Rigid Coulomb’s friction model is incorporated to handle sliding conditions. The developed kinematic contact-impact algorithm is incorporated into an explicit finite difference code previously developed by the authors. To validate the developed contact-impact algorithm, some numerical examples are illustrated. Comparisons between the kinematic contact algorithm and the exact solutions are made.